Harriet Beecher Stowe correspondence - Stowe, Harriet Beecher, 1811-1896.
Personal correspondence.
Abolitionist and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Abolitionists; Authors